First-Principles Study of Structure, Electronic and Optical Properties of HgSe in Zinc Blende (B3) Phase - Hamdollah Salehi; Firoozeh Anis Hoseini (Journal of Optoelectronical Nanostructures, 2019)
In this paper, the structural parameters, energy bands structure, density ofstates and charge density of HgSe in the Zincblende(B3) phase have been investigated.The calculations have been performed using the Pseudopotential method in theframework of density functional theory (DFT) by Quantum Espresso package. Theresults for the electronic density of states (DOS) show that the band gap for HgSe iszero. The obtained energy bands structure for HgSe show that the lowest conductionband minimum and the top of the valence band are degenerate at the center of Brillouinzone (Г),and this compound is a zero-gap material or semimetal. Calculation of electroncharge density in zincblende phase in (110) plane show that this compound has ionicand covalent bond simultaneously. The theoretical calculated optical properties andenergy Loss (EEL) spectrum yield a static refractive index of4.37and a plasmon energyof 22.83eV for cubic phase. This calculation are in good agreement with the othertheoretical and experimental values.